2001
DOI: 10.1007/s001250100589
|View full text |Cite
|
Sign up to set email alerts
|

Production and metabolic clearance of glucose under basal conditions in Type II (non-insulin-dependent) diabetes mellitus

Abstract: The relative importance of glucose over-production and inadequate peripheral removal in the postabsorptive (fasting) hyperglycaemia of Type II (non-insulin dependent) diabetes mellitus has produced diverse estimates. Some studies show that a strong correlation exists between fasting glucose concentrations and its production over a wide range of glycaemia, suggesting a causative role for excessive glucose output in hyperglycaemia [1,8]. Other measurements, however, show almost no correlation between glucose pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 14 publications
(35 reference statements)
6
33
2
Order By: Relevance
“…Elevated hepatic glucose production, due to increased gluconeogenesis, glycogenolysis, or both, is associated with the pathogenesis of type 2 diabetes (38,39). We found that basal hepatic glucose production was significantly decreased by rAd-GLP-1 treatment.…”
Section: Glp-1 Therapy In Obese Diabetic Micementioning
confidence: 67%
“…Elevated hepatic glucose production, due to increased gluconeogenesis, glycogenolysis, or both, is associated with the pathogenesis of type 2 diabetes (38,39). We found that basal hepatic glucose production was significantly decreased by rAd-GLP-1 treatment.…”
Section: Glp-1 Therapy In Obese Diabetic Micementioning
confidence: 67%
“…Should such adjustments be useful, the estimates of S I /S IN can be achieved on a population basis, which is the recommended venue for HOMA use. Interestingly, also, when morning fasting glucose levels are elevated as in type 2 diabetes, this appears to correspond to a high EGP, which declines during the day to near-normal rates (30). Glycemia decreases correspondingly.…”
Section: Possible Adjustmentsmentioning
confidence: 92%
“…They were admitted to the clinical investigation area at 12:00 h (day 1). Unprimed infusions of [U- 13 C]glucose and [3][4][5][6][7][8][9][10][11][12][13][14] C]lactate were initiated at 14.00 h. Sleep was again monitored during the night. The study continued until 14.00 h on day 2.…”
Section: Methodsmentioning
confidence: 99%
“…The resolution of this issue was based on the following observations: (1) glycaemia in type 2 diabetes is never constant, and so the assumption of a steady state could lead to quantitative inaccuracies [7,9]; and (2) EGP is elevated in the morning by 30-50% and decreases to near-normal rates by afternoon [4,7,8]. This results in a high degree of correlation between elevated glycaemia and EGP early in the morning and its dissipation by mid-afternoon [7,8]. The time of its determination is therefore critical to the conclusions drawn, as is the methodology used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation